A phase unwrapping method suitable for high frequency fringe based on edge feature. (November 2021) - Shi, Bo; Ma, Ziji; Ni, Xuefeng; Liu, Jianwei; Liu, Hongli
Highlights: We propose a high-efficiency method based on edge feature to recover the absolute phase map. An edge detection operator suitable for the wrapped phase map is explored. An edge point correction method is proposed to remove invalid edge points. A reverse fine correction method is presented to further optimize the fringe order. The proposed method requires at least three fringe patterns to unfold the wrapped phase map without any auxiliary fringe patterns. Abstract: Phase unwrapping (PU) technology is an important component of fringe projection profilometry (FPP). The key of PU is to obtain accurate fringe order. The existing PU methods are hard to make a tradeoff between efficiency and accuracy. To reduce the number of stripes, a phase unwrapping method based on edge feature (EFPU) is proposed. For this method, we make full use of the properties of wrapped phase map rather than auxiliary fringe patterns. We firstly analyze an edge detection operator suitable for wrapped phase map. Furthermore, in order to improve the stability of the proposed method, the edge correction method is proposed to correct edge point and the reverse correction method is presented to further optimize the fringe order. The experimental results show that the absolute phase map obtained by EFPU is similar to that of multi-wavelength phase-shifting (MWPS) method, but the number of fringe patterns is only one-third of MWPS.